The Effect of Project Based Learning Model on Creativity and Learning Outcomes of Basic Electrical Engineering - Mustafa, Andreas; Olii, Djami; Sangi, Nontje (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
This study aims to determine the effect of project based learning models on creativity and learning outcomes of Electrical Installation and Power Engineering students in the Basic Electrical Engineering subject in class XI of SMKN 1 Airmadidi This study used an experimental method with a post test only control group design The instruments used included learning outcome tests and creativity questionnaires The results showed a significant difference in the learning outcomes of Basic Electrical Engineering between students who were involved in learning using project based models and those who followed conventional methods This indicates that applying project based learning models substantially affects the learning outcomes of Basic Electrical Engineering in Class XI of SMKN 1 Airmadidi with a ttable< sub> value lt; tcount< sub> or 4 10 lt; 6 773 The project based model also shows the level of creativity between students who undergo learning with a project based approach and those who use conventional methods These findings indicate a significant effect of the project based learning model on student learning creativity in Class XI of SMKN 1 Airmadidi with a ttable < sub>value lt; tcount< sub> or 4 10 lt; 6 418 < p>